Evaluation of refractive errors in retinopathy of prematurity screening - Aida Pidro; Jasmina Alajbegović-Halimić; Nina Jovanović; Ajla Pidro (Medicinski glasnik, 2019)
Aim: To evaluate the frequency of refractive errors in premature children in retinopathy of prematurity (ROP) screening to find mutual connection of the prematurity level, disease activity and refractive errors. Methods: A retrospective study was conducted in the Eye Clinic of the University Clinical Centre Sarajevo, between December 2013 and January 2017. A total of 126 patients of gestational age ? 34 weeks and birth weight ? 2000 g underwent ROP screening program. The patients were divided into three groups: patients without ROP (n=15), patients with spontaneous regression (n=106) and those with active form of ROP (n=5). Results: There were 68 (54.0%) patients with refractive errors: 45 (35.7%) had hyperopia, 17 (13.5%) myopia and six (4.8%) astigmatism. There were three (60.0%) patients with an active form of ROP who had refractive errors: two (40.0%) had myopia and one (20.0%) hyperopia. The group without active ROP had hyperopia as most frequent refractive error, with 10 (66.7%) patients. The average birth weight of the patients without refractive errors was 1403.9±43.4 g compared to 1390.3±104.2 g of the patients with refractive errors (p=0.498). The average gestational age was 29.7±0.3 weeks in patients without and 29.0 ± 0.3 weeks in patients with refractive errors (p=0.126). Conclusion: The birth weight and the gestational age were significantly lower in patients with the active form of ROP. Lower gestational age and birth weight of premature children increase the chance for the development of refractive errors such as hyperopia in all premature children and myopia in patients with active form of ROP.
Keywords: hyperopia; myopia; astigmatism; preterm birth